Mechanical blade tenderization of meat - Burson, D.E.; Hayward, L.H.; Hunt, Melvin C.; Kastner, Curtis L.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station, 2011)
We randomly assigned 112 Angus yearling steers to 14 nutritional groups fed varied ration energy levels and varied lengths of time. Blade tenderized and non-tenderized boneless rib steaks were evaluated by a taste panel and a mechanical (Instron) shearing technique. Blade tenderization significantly improved taste panel sores for both muscle fiber and overall tenderness and decreased the amount of detectable connective tissue, but did not affect juiciness and flavor scores. Peak shear force decreased with blade tenderization; but total cooking loss increased. Blade tenderization narrowed the range of detectable connective tissue scores for ration energy level groups, leading to more uniform palatability.
Keywords: Beef; Blade tenderization; Palatability; Energy